1994
DOI: 10.1084/jem.179.2.703
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 5 synthesis by eosinophils: association with granules and immunoglobulin-dependent secretion.

Abstract: SummaryInterlenkin 5 (IL-5) is the main factor that promotes the terminal differentiation of eosinophil progenitors (as indicated by colony formation assays), and enhances the effector capacity of mature eosinophils. IL-5 is produced by T lymphocytes, CD4-/CD8-and mast cells and recently, messenger (m)RNA of this cytokine has been identified in eosinophils from patients with coeliac disease, asthma, or eosinophilic heart diseases. In this study, IL-5 mRNA and immunoreactive IL-5 protein were detected in tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
156
2
5

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(170 citation statements)
references
References 19 publications
7
156
2
5
Order By: Relevance
“…7 c). IL-5 plays an important role in eosinophil activation which may also serve as producers of this cytokine [46] . It is likely that the ability of PM exposure to provoke IL-5 secretion is in part responsible for the mobilization and accumulation of eosinophils in the lung, as we reported here.…”
Section: Discussionmentioning
confidence: 99%
“…7 c). IL-5 plays an important role in eosinophil activation which may also serve as producers of this cytokine [46] . It is likely that the ability of PM exposure to provoke IL-5 secretion is in part responsible for the mobilization and accumulation of eosinophils in the lung, as we reported here.…”
Section: Discussionmentioning
confidence: 99%
“…The eosinophil lineage appears to be specifically regulated by interleukin 5 (IL-5), a cytokine produced by the T helper 2 subset (Th2) as well as by eosinophils and mast cells. 2 Although earlier studies suggested additional activities of IL-5 in regulating mouse B cells and antibody production 3 recent studies with an IL-5 deficient mouse strain indicate that the regulation of eosinophilia may be the only obligatory role for IL-5 in the adult mouse. 4 IL-5 deficient mice, produced by gene targeting of embryonal stem cells, 4 appear to be normal in appearance and do not develop any obvious disease.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, eosinophils may mediate enhanced bronchial reactivity and damage to the respiratory epithelium by the secretion of major basic protein (MBP) (8 -10). In asthma, eosinophils may also localize to the airways mucosa, where they have the potential to prime and amplify the underlying immune responses that predispose to allergic inflammation by the secretion of cytokines (11)(12)(13)(14)(15)(16). Although there is accumulating evidence that eosinophils drive the pathogenesis of allergic disease under some circumstances, the mechanisms regulating their selective trafficking and degranulation in the airways have not been fully delineated.…”
mentioning
confidence: 99%